Persaingan Usaha di Tingkat Lokal: Tantangan Dan Peluang Bagi Pengusaha Kecil Dalam Menghadapi Pengusaha Lama - Afif Syafiuddin (Pusat Riset dan Inovasi Nasional, 2025)
Competition law is an important instrument in maintaining healthy and fair market dynamics, especially in the era of globalization marked by increasingly competitive economic growth. This article discusses how business competition takes place at the regional level, with particular attention to the obstacles faced by small entrepreneurs in facing the dominance of established companies. The competition that emerges is not only limited to price issues, but also involves difficulties in accessing capital, distribution networks, technology, and unfavorable regulations. Existing companies generally have strong structural strengths and networks, which create major barriers for new entrants. In addition, there are signs of unfair competitive practices that can threaten the survival of small businesses. However, advances in technology and digitalization are opening up new avenues for small entrepreneurs to enter the market and establish direct relationships with customers. This article aims to identify various forms of business competition at the local level, analyze the opportunities and challenges that exist, and develop strategies that encourage the creation of a healthy and inclusive competitive environment for the sustainability of local economic growth.